2013
DOI: 10.1111/jasp.12016
|View full text |Cite
|
Sign up to set email alerts
|

Something to chew on: psychosocial factors associated with oral health practices

Abstract: Although they can be prevented or reversed with proper oral hygiene, oral diseases are prevalent because oral self-care in the population is poor. Using structural equation modeling, we examined associations of theoretically guided psychosocial factors with oral health practices and dissatisfaction in young adults. Conscientiousness predicted lower dissatisfaction (b = -.35, p < .05); oral health self-efficacy predicted lower dissatisfaction (b = -.52, p < .05) and better oral health practices (b = .89, p < .0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This result is consistent with the outcome of discriminant validity. A previous study showed that task‐specific oral health self‐efficacy is a strong positive indicator of oral health practices and is inversely predictive of dissatisfaction with oral health . Self‐efficacy is strongly associated with better oral health practices and lower dissatisfaction.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This result is consistent with the outcome of discriminant validity. A previous study showed that task‐specific oral health self‐efficacy is a strong positive indicator of oral health practices and is inversely predictive of dissatisfaction with oral health . Self‐efficacy is strongly associated with better oral health practices and lower dissatisfaction.…”
Section: Discussionmentioning
confidence: 95%
“…Self‐efficacy is strongly associated with better oral health practices and lower dissatisfaction. Those who felt confident in taking care of their teeth and gums and received oral health care were more likely to do so and were more satisfied with their oral health status . The respondents with caries tended to have poorer satisfaction with oral health than those without.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women can, however, mobilize social support to moderate the effect of stress better than men [20][21][22][23]. These psychosocial factors have implications for oral health [24] and are associated with maternal morbidities during the young-child-care period [25][26][27].…”
Section: Introductionmentioning
confidence: 99%